1985
DOI: 10.1099/00221287-131-10-2533
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Saccharomyces cerevisiae against Cd2+ Toxicity by Ca2+

Abstract: Ca)+ protected yeast cells very effectively against the toxic effects of Cd2+; Mg2+ had only a slight protecting effect as far as protection against Cd'+-induced release of K + was concerned. Protection of the yeast cells against Cd'+ toxicity was due to a reduction in Cd'+ uptake in the presence of Ca2+. A single relationship existed between the relative rate of K+ release induced by Cd2+ and the celldar Cd'+ concentration. Within the first few minutes of incubating cells with Cd'+, the molar ratio of K+ rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
1
20
1
2
Order By: Relevance
“…The specific activities of Io9Cd and 4sCa were 0.9 Ci mmol-' (33.3 GBq mmol-') and 9.2 mCi mmol-I (340.4 MBq mmol-I), respectively. Nitrogen was bubbled through the suspension at 25 "C and at appropriate times 2 ml samples were filtered and washed (Kessels et al, 1985). Radioactivity on the filters was determined by liquid scintillation counting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific activities of Io9Cd and 4sCa were 0.9 Ci mmol-' (33.3 GBq mmol-') and 9.2 mCi mmol-I (340.4 MBq mmol-I), respectively. Nitrogen was bubbled through the suspension at 25 "C and at appropriate times 2 ml samples were filtered and washed (Kessels et al, 1985). Radioactivity on the filters was determined by liquid scintillation counting.…”
Section: Methodsmentioning
confidence: 99%
“…Cd2+ is very toxic to all kinds of living cells including yeasts (Norris & Kelly, 1977;Gadd & Mowl, 1983;Kessels et al, 1985;Heldwein et al, 1977;Macara, 1978;Bitton et ul., 1984). Not only is growth inhibited but Cd2+ also provokes K+ loss from metabolizing yeast cells (Norris & Kelly, 1977;Gadd & Mowl, 1983;Kessels et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of intracellular and extracellular magnesium concentrations on heavy metal toxicity has been described in several studies, although the mechanisms have not been elucidated. A general protective effect of magnesium against heavy-metal cations such as manganese, copper, nickel, cadmium and cobalt in yeast ( Blackwell et al, 1998, Karamushka and Gadd, 1994, Joho et al, 1991, Kessels et al, 1985and Norris and Kelly, 1979, and zinc and cadmium in plants ( Pedler et al, 2004 andKupper andKochian, 2010) has been reported. In particular, the uptake of divalent cations in yeast was reduced by the addition of extracellular magnesium ( Pisat et al, 2009, Blackwell et al, 1998and Bianchi et al, 1981.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals may damage the yeast cell membrane by fluidizing it, which causes potassium channels to open and its intracellular level to decrease 4,9,16 .…”
Section: Introductionmentioning
confidence: 99%